Analisis Penyebab dan Strategi Guru Wali Kelas Mengatasi Kesulitan Membuat Pertanyaan MIS Al-Mushthafawiyah Medan - Maulidah Hasnah Anas (putrapublisher.org, 2023)
The purpose of this study is to analyze the difficulties of class V students of MIS Al-Mushthafawiyah in making questions in Indonesian language lessons and to find out the homeroom teacher's strategy in overcoming difficulties in asking questions. This type of research is descriptive qualitative. The study was conducted in the odd semester of the 2022-2023 school year. Primary data sources are students and homeroom teachers MIS Al-Mushthafawiyah and secondary data sources of books, journals, websites that are in accordance with the research title. Data collection uses observation, documentation, interview, and test methods. Data analysis techniques use data reduction, data presentation, and data verification. Testing Data validity: Source triangulation, and technical triangulation. The results of the study mentioned difficulties in making questions; Lack of understanding of the contents of the reading, lack of motivation, lack of concentration, lack of varied methods, lack of understanding in placing question words. Facing this, the homeroom teacher views it is necessary to set a more appropriate learning strategy. Strategies implemented; A special approach by inviting students to communicate, collaborate methods, provide additional hours, provide rewards, enthusiasm and motivation, invite parents/guardians of students to accompany students in learning